The GABAA Receptor Influences Pressure Overload-Induced Heart Failure by Modulating Macrophages in Mice - Jin Bu; Shiyuan Huang; Jue Wang; Tong Xia; Hui Liu; Ya You; Zhaohui Wang; Kun Liu (Frontiers in Immunology, 2021)
BackgroundMyocardial macrophages have key roles in cardiac remodeling and dysfunction. The gamma-aminobutyric acid subtype A (GABAA) receptor was recently found to be distributed in macrophages, allowing regulation of inflammatory responses to various diseases. This study aimed to clarify the role of GABAA receptor-mediated macrophage responses in pressure overload-induced heart failure.Methods and ResultsC57BL/6J mice underwent transverse aortic constriction for pressure-overload hypertrophy (POH) and were intraperitoneally treated with a specific GABAA receptor agonist (topiramate) or antagonist (bicuculline). Echocardiography, histology, and flow cytometry were performed to evaluate the causes and effects of myocardial hypertrophy and fibrosis. Activation of the GABAA receptor by topiramate reduced ejection fraction and fractional shortening, enlarged the end-diastolic and end-systolic left ventricular internal diameter, aggravated myocardial hypertrophy and fibrosis, and accelerated heart failure in response to pressure overload. Mechanistically, topiramate increased the number of Ly6Clow macrophages in the heart during POH and circulating Ly6Chigh classic monocyte infiltration in late-phase POH. Further, topiramate drove Ly6Clow macrophages toward MHCIIhigh macrophage polarization. As a result, Ly6Clow macrophages activated the amphiregulin-induced AKT/mTOR signaling pathway, and Ly6ClowMHCIIhigh macrophage polarization increased expression levels of osteopontin and TGF-β, which led to myocardial hypertrophy and fibrosis. Conversely, GABAA receptor blockage with bicuculline reversed these effects.ConclusionsControl of the GABAA receptor activity in monocytes/macrophages plays an important role in myocardial hypertrophy and fibrosis after POH. Blockade of the GABAA receptor has the potential to improve pressure overload-induced heart failure.